Efektivitas Bimbingan Kelompok Teknik Home Room Untuk Mencegah Dampak Negatif Berpacaran Di Smk Pgri 1 Kudus - slamet, agung; Prabowo, Wisnu; Hidayati, Richma (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2025)
The objectives of this study are: 1. To determine the improvement of students' understanding before and after being given Homeroom engineering group guidance services to students in grade X MPLB 3 SMK PGRI 1 Mejobo Kudus., 2. To find out the effectiveness of the implementation of homeroom engineering group guidance services to prevent the negative impact of dating on students by using Group Guidance. The research uses the quasi-experiment method of design one group pretest and posttest. This research was carried out in class X MPLB 3 by conducting a pretest to find out the number of research subjects needed for treatment and after the pretest was carried out. The results of the study showed that before group guidance with the homeroom technique (pretest) the understanding of the negative impact of dating tended to be low with an average of 71.5 and after being given the treatment of group guidance services with the homeroom technique (posttest) the understanding of the negative impact of dating experienced a significant increase.